New Methodologies for Patients Rehabilitation - Fardoun, H. M.; Mashat, A. S.; Lange, B. (Methods of Information in Medicine, 2015)
Objective: The present editorial is part of the focus theme of Methods of Information in Medicine titled “New Methodologies for Patients Rehabilitation”, with a specific focus on technologies and human factors related to the use of Information and Communication Technologies (ICT) for improving patient rehabilitation.Methods: The focus theme explores different dimensions of empowerment methodologies for disabled people in terms of rehabilitation and health care, and to explores the extent to which ICT is a useful tool in this process.Results: The focus theme lists a set of research papers that present different ways of using ICT to develop advanced systems that help disabled people in their rehabilitation process.
Keywords: Virtual rehabilitation; multi-user systems for user interaction; virtual humans; communications aids; training tools for rehabilitation; rehabilitation robotics